2019
DOI: 10.1155/2019/9812651
|View full text |Cite
|
Sign up to set email alerts
|

Model and Resilience Analysis for Handling Chain Systems in Container Ports

Abstract: Container ports are critical components of global port and shipping supply chain (PSSC) systems. Their handling operation resiliencies can affect their performance, along with those of the overall port and shipping supply chain. According to the characteristics of the container handling operations, this study establishes a modeling paradigm for quantifying the resilience of handling chain system (HCS) in container ports. Considering the nonnegative arrive rate and the container handling completion rate, with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…Our nonlinear model extends the nonlinear model of Xu et al in that our model explicitly considers the unsatisfied freight requirement constraint, whereas the model of Xu et al assumed that the value of the unsatisfied freight requirement may be negative, although it does not exist in the actual operation [5]. Under real environments of container ports, the value of arate(t) cannot be negative, although mathematically it holds; the upper value of comrate(t) is limited; fr(t) is not constant; ufr(t) should not be negative even in the case of a sharp drop in fr(t).…”
Section: Nonlinear Modelmentioning
confidence: 99%
See 3 more Smart Citations
“…Our nonlinear model extends the nonlinear model of Xu et al in that our model explicitly considers the unsatisfied freight requirement constraint, whereas the model of Xu et al assumed that the value of the unsatisfied freight requirement may be negative, although it does not exist in the actual operation [5]. Under real environments of container ports, the value of arate(t) cannot be negative, although mathematically it holds; the upper value of comrate(t) is limited; fr(t) is not constant; ufr(t) should not be negative even in the case of a sharp drop in fr(t).…”
Section: Nonlinear Modelmentioning
confidence: 99%
“…Xu et al modeled the nonlinear handling chain in the container port with control approach. In addition, the authors demonstrated a starting point in the development of a quantitative resilience decision-making framework and mitigating the negative impacts for port authorities and other players in the port and shipping supply chain [5]. However, the exiting models and solution approaches have the following limitations that might hinder practical applications: (i) their model relies on highly simplified assumptions that reducing the complexity of the problem; as a result, the accuracy of their models may vary a lot under different dynamical conditions, and (ii) since their solution method is not a practically applicable exact approach, the method may incur unsatisfied freight service requests even if the handling plans proposed by the port operators are feasible; as a result, the port operators may need to revise their plans frequently, which is undesirable in practice.…”
Section: Motivation For Workmentioning
confidence: 99%
See 2 more Smart Citations
“…However, accompanied with the deterioration of the global economic and trade environment, container ports are facing more challenges, such as fiercer and fiercer competition, improving the service level, attracting freight source, saving operation cost, promoting operation efficiency (He etc., 2019) [1]. The resilient and efficient container handling chain system (HCS) has been presented as an opportunity to improve the operations and performances of container port simultaneously (Xu etc., 2019) [2]. Because of these benefits, the container handling chain system has attracted much attention from port authorities and other players in the port and shipping supply chain, and researchers worldwide.…”
Section: Introductionmentioning
confidence: 99%